2021
DOI: 10.3390/polym13091492
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing Para-Aramid Textiles Pretreated with Soybean Oil and Nonthermal Plasma Using Cationic Dye

Abstract: The increasing use of functional aramids in a wide array of applications and the inert nature of aramids against conventional dye and print methods requires developing new dyeing methods. This study aims to use environmentally friendly method with a cationic dye as an alternative for dyeing para-aramid fabrics. Experiments used a multi-factorial design with functions of pretreatment, dye solvent (water and/or glycerol) and auxiliary chemical additives (swelling agent and surfactant) and a sequential experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…TWEEN was the only factor not involved in any significant interactions; the addition of the surfactant negatively affected dyeing performance, consistent with our previous observations [ 9 , 10 ]. The surfactant, although helping to form a dye dispersion, might also hinder the diffusion of the dye onto the para-aramid fiber fabrics.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…TWEEN was the only factor not involved in any significant interactions; the addition of the surfactant negatively affected dyeing performance, consistent with our previous observations [ 9 , 10 ]. The surfactant, although helping to form a dye dispersion, might also hinder the diffusion of the dye onto the para-aramid fiber fabrics.…”
Section: Resultssupporting
confidence: 91%
“…It is interesting to observe that at AA/Soy = 1.6, a 30 s NTP treatment after dyeing greatly decreased color strength, whereas at AA/Soy = 4 there was no change. A plausible explanation would be that NTP could quickly degrade the dye molecules [ 10 ]; however, at higher AA/Soy, more chemical functionalities could absorb most NTP energy and reactive species, thus protecting the dye from degradation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies attempted surface modification of para‐aramid fabrics with nonthermal plasma (NTP), and we concluded that NTP treatment alone would not significantly enhance the dyeability using a conventional dye bath. Nonetheless, we demonstrated that pretreatment with soybean oil or biopolymers derived from soybean oil followed by NTP treatment enabled dyeing para‐aramids to significantly higher color strength without other chemical additives in a conventional dye bath; and this new method is compatible with both a disperse dye and a cationic dye (Morris et al; Morris et al, 2021a).…”
Section: Introductionmentioning
confidence: 96%